Immunosurveillance and immunoediting in MMTV-PyMT-induced mammary oncogenesis. (1st February 2017) - Gross, Emilie T. E.; Han, Semi; Vemu, Prasantha; Peinado, Carlos D.; Marsala, Martin; Ellies, Lesley G.; Bui, Jack D.
ABSTRACT: Evidence of cancer immunosurveillance and immunoediting processes has been primarily demonstrated in mouse models of chemically induced oncogenesis. Although these models are very tractable, they are characterized by high mutational loads that represent a minority of human cancers. In this study, we sought to determine whether cancer immunosurveillance and immunoediting could be demonstrated in a more clinically relevant oncogene-induced model of carcinogenesis, the MMTV-PyMT (PyMT) mammary carcinoma model. This model system in the FVB/NJ strain background was previously used to demonstrate that adaptive immunity had no role in limiting primary cancer formation and in fact promoted metastasis, thus calling into question whether cancer immunosurveillance operated in preventing the development of breast cancer. Our current study in the C57BL/6 strain backgrounds provides a different conclusion, as we report here the existence of an adaptive immunosurveillance of PyMT mammary carcinomas using two independent models of immune deficiency. PyMT mice bred onto a Rag1 −/− background or immune suppressed by chronic tacrolimus therapy both demonstrated accelerated development of mammary carcinomas. By generating a bank of cell lines from these animals, we further show that a subset of PyMT cell lines had delayed growth after transplantation into wild-type (WT) syngeneic, but not immune-deficient hosts. This reduced growth rate in immunocompetent animals was characterized by an increase in immune cell infiltration and tissue differentiation. Furthermore, loss of the immune cell infiltration that characterized immunoediting of slow growing cell lines, changed them into fast growing variants capable of progressing in the immunocompetent model. In conclusion, our study provides evidence that immunosurveillance and immunoediting of PyMT-derived cell lines modulate tumor progression in this oncogene-induced model of cancer.